Pengaruh Ekspor Migas, Penanaman Modal Dalam Negeri dan Inflasi Terhadap Pertumbuhan Ekonomi di Provinsi Jawa Timur Tahun 1999-2019 - Elma Sintia Dewi; Aris Soelistyo; Dwi Susilowati (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
Economic growth is one indicator in seeing the success of a region's development. By knowing economic growth, regions can determine regional development strategies and plans by taking into account the factors that influence economic growth, both which have positive and negative impacts from year to year. Several factors that can affect economic growth are exports, investment and inflation. This study aims to determine and explain the effect of oil and gas exports, domestic investment and inflation on economic growth in East Java in 1999 - 2019. The study uses GRDP data based on constant prices, Oil and Gas Exports, Domestic Investment and Inflation in East Java Province. 1999 - 2019. The method of analysis in this study is multiple linear regression analysis. The results showed that Oil and Gas Exports, Domestic Investment and Inflation had a considerable influence on the East Java economy by 0.866 or 86.68 percent. The conclusion is that oil and gas exports and domestic investment have a positive impact, while the inflation variable has a negative impact on economic growth in East Java.